Equity, Informed Consent, and Ethical Challenges in Nutrigenetics-Based Precision Nutrition - Loury Priskila; Hendi Wicaksono; Amaze Grace Sira; Fenita Renny Dinata; Michael Reskiantio Pabubung (PT Dexa Medica, 2026)
Background: Precision nutrition represents a paradigm shift from generalized dietary recommendations to individualized interventions based on genetic, metabolic, and environmental profiles, offering significant potential for the prevention and management of chronic diseases. Methods: A comprehensive literature search was conducted using PubMed and Google Scholar to evaluate the current landscape of the field. This review analyzed peer-reviewed articles, systematic reviews, and randomized controlled trials published between 2010 and 2025, focusing specifically on the ethical considerations, accessibility, and clinical integration of nutrigenetics. Results: Findings indicate that despite its promise, nutrigeneticsbased precision nutrition faces substantial limitations. Scientific validity remains inconsistent, particularly within direct-toconsumer (DTC) genetic testing. Ethical concerns are prominent regarding informed consent, which is often reduced to complex digital agreements that obscure data use, privacy risks, and issues related to autonomy in vulnerable populations. Furthermore, equity challenges persist; high costs and digital literacy gaps threaten to transform precision nutrition into an exclusive service. This is compounded by algorithmic biases stemming from the underrepresentation of diverse populations in genomic datasets, which risks generating inaccurate recommendations and exacerbating existing health disparities. Conclusion: While nutrigenetics-based precision nutrition offers transformative opportunities for personalized healthcare, its responsible implementation requires strengthened regulatory frameworks, improved genetic literacy among healthcare professionals, transparent consent processes, and inclusive data practices to ensure equitable integration into clinical and public health systems.